Repeated moral hazard and contracts with memory: A laboratory experiment - Petra Nieken; Patrick W. Schmitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper reports data from a laboratory experiment on two-period moral hazard problems. The findings corroborate the contract-theoretic insight that even though the periods are technologically unrelated, due to incentive considerations principals can benefit from offering long-term contracts that exhibit memory.
urn:nbn:de:bvb:19-epub-13182-0
Keywords: D82; J33; 330; Repeated moral hazard; Sequential hidden actions; Laboratory experiment; Moral Hazard; Vertragsrecht; Zeit; Test